Negative Effects of Mobile Phone Addiction Tendency on Spontaneous Brain Microstates: Evidence From Resting-State EEG - Li, Hao; Yue, Jingyi; Wang, Yufeng; Zou, Feng; Zhang, Meng; Wu, Xin (Frontiers in Human Neuroscience, 2021)
The prevalence of mobile phone addiction (MPA) has increased rapidly in recent years, which has a certain negative impact on emotions(e.g. anxiety, depression) or cognitive capacities(such as executive control, working memory). At the level of neural circuits, the continued increase in activity in the brain regions associated with addiction leads to neural adaptations and structural changes. At present, spontaneous brain microstates which could be negative influenced by MPA were unclear. In this study, the temporal characteristics of four resting-state EEG (RS-EEG) microstates (MS1, MS2, MS3, MS4) related to mobile phone addiction tendency (MPAT) were investigated by using mobile phone addiction tendency scale (MPATS). We attempted to analyze the correlation between MPAT and corresponding microstates, and provide evidence to explain the brain and behavioral changes caused by MPA. The results showed that the total score of MPATS were positively correlated with the duration of MS1 related to phonological processing, and negatively correlated with duration of MS2 related to visual or imagery processing and MS4 related to attentional network; the score of withdrawal symptoms subscale were additionally associated with duration of MS3 related to cingulo-opercular emotional network. Based on these results, we thought that MPAT might have some negative effects on attentional networks and sensory brain networks; moreover, withdrawal symptoms might induce some negative emotion.